JARGON CAPRES – CAWAPRES FIKTIF; NURHADI – ALDO DALAM WACANA PRA-PEMILU DI INDONESIA TAHUN 2019 - I Gede Dwi Setiadi (Universitas Warmadewa, 2019)
[Title: The Jargon of Presidential and Vice Presidential Candidate; Nurhadi-Aldo in the Pre-Election Discourse in Indonesia in 2019] This study discusses the phenomenon of the emergence of the fictional vice-presidential candidate Nurhadi-Aldo in the midst of the heat of the situation in 2019 pre-election Indonesian politics with a number of unique jargon. The uniqueness of jargon is the result of the words that are used so it is interesting to discuss the meaning and structure of the sentence. This study uses a theory that is discourse analysis theory to find the meaning of these jargon. The theory of discourse analysis consists of three structures, namely (1) macro structure, (2) superstructure, and (3) microstructure. The macro structure consists of thematic observation domains or themes. The superstructure consists of a schematic field of observation, namely how the structure and elements of the discourse are arranged in full text. The micro structure consists of the domains of observation (a) semantics, (b) syntax, (c) stylistics, and (d) rhetorical. However, in this study the realm of syntactic observation is not used because it is considered that no data can be examined.